Partition Dimension of Dutch Windmill Graph: Dimensi Partisi Graf Kincir Angin Belanda untuk siklus orde besar (Jurnal Matematika, Statistika dan Komputasi, 2021)
Let be a connected graph G and -partition of  end . The coordinat to  is definition . If every twovertex is distinct  applies, then  is a called  partition of . The minimum k for which k-resolving partition of  is the partition dimension  and denoted with . In this paper, we investigates the partition dimensionfor a large Dutch windmill graph  for  and . We show that if  for some, forany.
Keywords: Partition Dimension; Amalgamation; Cycle Graph